Implementation of the MQ135 Sensor for Carbon Monoxide Measurement in Air - Fadhillah (Journal of Holistic Medical Technologies (JHMT), 2025)
The increase in air pollution caused by industrial activities, transportation, and urbanization has led to a decline in air quality, particularly in urban areas. Carbon monoxide (CO) is one of the hazardous gases that can harm human health. This article discusses the use of the MQ135 sensor to measure CO concentration in the air, which is then monitored in real time through the Blynk application. The MQ135 sensor was calibrated using CO gas samples to ensure accurate readings. The test results showed that the sensor could quickly detect changes in CO concentration, and the Blynk application displayed the data directly in an easy-to-understand graphical form. These tests demonstrated that the developed system works effectively. A stable Wi-Fi connection on the ESP8266 module also ensured uninterrupted data transmission to the application. This implementation highlights the potential for real-time air quality monitoring, which is highly beneficial for managing air pollution and protecting public health.